2018
DOI: 10.1002/adfm.201805184
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between Structural and Thermoelectric Properties in Epitaxial Sb2+xTe3 Alloys

Abstract: In recent years strain engineering is proposed in chalcogenide superlattices (SLs) to shape in particular the switching functionality for phase change memory applications. This is possible in Sb 2 Te 3 /GeTe heterostructures leveraging on the peculiar behavior of Sb 2 Te 3 , in between covalently bonded and weakly bonded materials. In the present study, the structural and thermoelectric (TE) properties of epitaxial Sb 2+x Te 3 films are shown, as they represent an intriguing option to expand the horizon of str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 53 publications
3
20
0
Order By: Relevance
“…Compared to Sb 2 Te 3 , with higher interlayer distances and weaker interactions, there are not many exfoliation works reported too. High‐quality sheets of Sb and Sb 2 Te 3 have been obtained by epitaxial growth, mechanical and/or liquid‐phase exfoliation methods.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to Sb 2 Te 3 , with higher interlayer distances and weaker interactions, there are not many exfoliation works reported too. High‐quality sheets of Sb and Sb 2 Te 3 have been obtained by epitaxial growth, mechanical and/or liquid‐phase exfoliation methods.…”
Section: Introductionmentioning
confidence: 99%
“…Electronic and lattice dynamics in chalcogenide-based materials are important factors in the performance of opto-electrical data-storage media and thermoelectric devices. Among these materials, Sb 2 Te 3 is a prototype as it is, together with GeTe and BiTe, one of the constituents of chalcogenide superlattices (CSLs) 1 , 2 . Combining Sb 2 Te 3 with one of the above-mentioned crystals together in one lattice, creates a superlattice with intriguing properties different or greater than those of its individual components.…”
Section: Introductionmentioning
confidence: 99%
“…Combining Sb 2 Te 3 with one of the above-mentioned crystals together in one lattice, creates a superlattice with intriguing properties different or greater than those of its individual components. In a recent study it has been demonstrated that a strong link exists among structural and thermoelectric properties in epitaxial Sb 2+ x Te 3 , the latter having implications also in phase change SLs upon strain engineering in designed Sb 2+ x Te 3 /GeTe multilayers 1 . Improved thermoelectric properties by nanostructuring Sb 2 Te 3 /BiTe multilayer have already been demonstrated 3 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Between each annealing step, the samples were investigated by means of X‐ray diffraction (XRD) and Raman spectroscopy. In the recent years Raman spectroscopy was extensively exploited by our group to investigate GST, Sb 2 Te 3 /GeTe and Sb 2 Te 3 /GST SLs, and most recently Sb 2+x Te 3 alloys . Different annealing conditions are tested, allowing to identify T x and to optimize a recipe to reduce the segregation.…”
mentioning
confidence: 99%